Review: Andrew Hopper and Philip Major, eds., England's Fortress: New Perspectives on Thomas, 3rd Lord Fairfax (Farnham, Surrey, and Burlington, VT: Ashgate, 2014), xv + 290; 20 illus. $149.95. Issue 1 (2016) - Hirst, Derek
No abstract available